Facile synthesis of CeO2 nanoparticles for enhanced removal of malachite green dye from an aqueous environment. Issue 2 (4th January 2023) - Borgohain, Xavy; Das, Emee; Rashid, Md. Harunar
Abstract : We present a co-precipitation approach for the synthesis of smaller-sized CeO2 nanoparticles for enhanced removal of malachite green dye from water. Abstract : The discharge of toxic synthetic dyes into industrial effluents has emerged as a significant environmental issue that requires attention. The goal of this work is to develop an environmentally acceptable material that could be used for the removal of malachite green dye from aqueous solutions very effectively. Accordingly, we present here the synthesis of smaller-sized CeO2 nanoparticles (NPs) by the co-precipitation method in the absence of any additive at 60 °C for 30 min. The diffractometric analysis confirmed the formation of pure CeO2 NPs possessing a fluorite-type fcc structure. The microscopic analysis confirmed the formation of spherical particles of sizes less than 10 nm. The surface areas of the as-prepared CeO2 NPs are varied from 159.6 m 2 g −1 to 189.3 m 2 g −1 as confirmed by the N2 gas adsorption–desorption study. Batch studies under various adsorbent loadings, contact times, initial dye concentrations and pH values were undertaken to investigate the malachite green dye adsorption performance by the CeO2 NPs. Under the optimized conditions, approximately 98.0% of malachite green dye could be removed from the aqueous solution within 120 min using CeO2 NPs. The adsorption of malachite green dye on the CeO2 NPs follows pseudo-second-order kinetics. Both the Langmuir model and the Sips model can be used to fit the isotherm data with the maximum adsorption capacity according to the Langmuir isotherm ( q m ), and the Sips isotherm ( q ms ) being 558.68 mg g −1 at 313 K and 740.54 mg g −1 at 303 K, respectively. The CeO2 NPs are stable and reusable up to the fifth cycle with little decrease in the adsorption performance.